Synthesis and Crystal Structure of a New Mononuclear Complex: [Cd(C10H12N2O)2(NO3)2(H2O)2] - CHU*, ZHAO-LIAN; DONG†, HUA-ZE (Asian Journal of Chemistry, 2024)
A novel three-dimensional hydrogen-bonding mononuclear complex [Cd(C10H12N2O)2(NO3)2(H2O)2], where C10H12N2O is 3-(dimethylamino)- 1-(pyridin-4-yl)prop-2-en-1-one, was synthesized and characterized by IR spectra, elemental analysis and single-crystal X-ray. The crystal structure analysis shows that the cadmium(II) is a six-coordinated in a slightly distorted octahedral geometry environment. The crystal is monoclinic, space group C2/c with unit cell parameters: a = 22.000(3)Å, b = 8.574(12)Å, c = 14.532(2)Å, α = 90º, β = 114.643(2)º, γ = 90º, V = 2491.6(5)Å3, Z = 4, Mr = 620, Dc = 1.666 Mg/cm3, μ = 0.942 mm-1, F(000) = 1272, T = 273(2) K, R = 0.0417, wR = 0.0954 for 2184 reflections with I > 2σ(I).